Evaluation of the plasmatic and parenchymal elution kinetics of two different irinotecan-loaded drug-eluting embolics in a pig model - Gnutzmann, Daniel; Mechel, Julia; Schmitz, Anne; Bellemann, Nadine; Gockner, Theresa; Mokry, Theresa; Kortes, Nikolas; Sommer, Christof-Matthias; Kauczor, Hans-Ulrich; Radeleff, Boris; Stampfl, Ulrike (Journal of vascular and interventional radiology, 2015)
To evaluate and compare irinotecan elution kinetics of two drug-eluting embolic agents in a porcine model. Embolization of the left liver lobe was performed in 16 domestic pigs, with groups of two receiving 1 mL of DC Bead M1 (70-150 µm) or Embozene TANDEM (75 µm) loaded with 50 mg irinotecan. Irinotecan plasma levels were measured at 0, 10, 20, 30, 60, 120, 180, and 240 minutes after completed embolization and at the time of euthanasia (24 h, 48 h, 72 h, or 7 d). Liver tissue samples were taken to measure irinotecan tissue concentrations. The highest irinotecan plasma concentrations of both embolic agents were measured 10 and 20 minutes after embolization, and concentrations were significantly higher for DC Bead M1 versus Embozene TANDEM (P = .0019 and P = .0379, respectively). At 48 hours and later follow-up, no irinotecan was measurable in the plasma. For both embolic agents, the highest irinotecan tissue concentration was found after 24 hours and decreased in a time-dependent manner at later follow-up intervals. Additionally, SN-38 tissue levels for both agents were therapeutic at 24 hours, with therapeutic levels of SN-38 at 48 hours in one liver embolized with TANDEM particles. Histopathologic analysis revealed ischemic, inflammatory, and fibrotic tissue reactions. Irinotecan is measurable in plasma and hepatic tissue after liver embolization with both types of irinotecan-eluting embolic agents. DC Bead M1 shows early burst elution kinetics, whereas Embozene TANDEM has a lower and slower release profile. The initial burst is significantly greater after embolization with DC Bead M1 than with Embozene TANDEM.